2015
DOI: 10.1002/eji.201545832
|View full text |Cite
|
Sign up to set email alerts
|

AIDing cancer treatment: Reducing AID activity via HSP90 inhibition

Abstract: The activation induced deaminase (AID) catalyses the two key events underlying humoral adaptive immunity: class switch recombination and somatic hypermutation of antibody genes in B lymphocytes. AID accomplishes this task by directly deaminating cytosines within the genomic immunoglobulin locus, thereby triggering a complex mutagenic process eventually leading to improved effector function of antibodies. However, it has long been noticed that AID can be aberrantly expressed in cancer and that its activity is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…as TLR and IFN signaling, to suppress L1s, in turn leading to hypermutation and increased RNA editing (Blanc and Davidson 2010;Roberts et al 2013;Rebhandl and Geisberger 2015;Orecchini et al 2017), and ultimately increasing the risk of impairing immune genes.…”
Section: Discussionmentioning
confidence: 99%
“…as TLR and IFN signaling, to suppress L1s, in turn leading to hypermutation and increased RNA editing (Blanc and Davidson 2010;Roberts et al 2013;Rebhandl and Geisberger 2015;Orecchini et al 2017), and ultimately increasing the risk of impairing immune genes.…”
Section: Discussionmentioning
confidence: 99%
“…The above observations suggest a possibility of using 17-AAG in the treatment of hypomethylated lymphomas (Figure 1 ). In a recent study 17-DMAG, a derivative of 17-AAG, has been found to reduce CSR and SHM in mice, while B-cell survival and proliferation remain unaffected ( 172 ).…”
Section: Epigenomic Role Of Immune Diversification In Disease Developmentioning
confidence: 99%
“…Aside of these on-target activities, AID was also shown to perform substantial off-target effects by mediating genome wide mutations (off-target hypermutation) and translocations (off-target CSR) [3]. These off-target effects significantly contribute to lymphomagenesis as well as to clonal evolution and treatment resistance [4, 5]. Apart from these well described mutagenic effects, AID was also shown to contribute to DNA demethylation by deaminating methylated cytosines, thereby generating thymines, which are eventually replaced by unmethylated dCs by the DNA mismatch repair machinery independent of proliferation or DNA replication [6].…”
Section: Introductionmentioning
confidence: 99%